1986
DOI: 10.1182/blood.v68.2.493.493
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of hairy cell leukemia with recombinant alpha-interferon

Abstract: Thirty patients with hairy cell leukemia were treated with recombinant interferon alpha-A (rIFN alpha A; Roferon-A); seven were previously untreated. Nine complete and 17 partial remissions were documented by bone marrow core biopsies. All patients' peripheral blood hematologic indexes either improved or normalized. Twelve of 13 patients with retroperitoneal or mediastinal adenopathy obtained remissions of tumor masses. All seven patients with splenomegaly showed prompt reduction in the size of the spleen to n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(53 citation statements)
references
References 8 publications
1
52
0
Order By: Relevance
“…Nine (30%) CR and 17 (56%) PR were confirmed by bone marrow core biopsies. All patients' peripheral blood hematologic indices either improved or normalized [33]. A multicenter phase II study of 64 patients published in 1986 confirmed the drug's efficacy in hairy cell leukemia [34].…”
Section: Hairy Cell Leukemiamentioning
confidence: 79%
“…Nine (30%) CR and 17 (56%) PR were confirmed by bone marrow core biopsies. All patients' peripheral blood hematologic indices either improved or normalized [33]. A multicenter phase II study of 64 patients published in 1986 confirmed the drug's efficacy in hairy cell leukemia [34].…”
Section: Hairy Cell Leukemiamentioning
confidence: 79%
“…However, glyco-peptides containing L28N were not detected by mass spectrometry, suggesting that the site may have remained unmodified. According to the recent cryo-EM structure of oligosaccharyltransferase (OST) [34][35][36], which catalyzes the initial transfer of glycan from the [37][38][39]. IFNβ is a well-known treatment for multiple sclerosis, with a number of different versions available (Rebif -IFNβ 1a, liquid form, Avonex -IFNβ 1a, lyophilized, Cinnovex -IFNβ 1a, biogeneric, Betaseron -IFNβ 1b, Plegridy -PEGylated IFNβ 1a) [40][41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical relapses have been observed in 33% to 48% of patients with HCL after interferon treatment, and the median time to disease progression after cessation of interferon therapy has ranged from 6 to 25 months. 44,50,56,57 The disease-free survival rate at 2 years has ranged from 25% to 60% in different ~e r i e s .~" ,~~ Patients with a neutrophil alkaline phosphatase (NAP) level of less than 30 have had a median failure-free survival time of 30.4 months, compared with 12.4 months in patients with greater than 30% hairy cells in the bone marrow and a NAP of 30 or more.56 A median failure-free survival time of 23.5 months has been observed in patients with a NAP of 30 or more and 30% or fewer hairy cells. Patients who express the CD5 antigen have been found to respond poorly to i n t e r f e r~n .~~…”
Section: Interferonsmentioning
confidence: 99%